Penerapan Pembelajaran Penyelesaian Masalah terhadap Keterampilan Pemecahan Masalah Peserta Didik - Ratna Dewi; Muh. Tawil; Salma Samputri (Universitas Negeri Makassar, 2025)
This study aims to (1) determine the magnitude of the increase in students' problem solving skills before and after applying the problem solving learning model. (2) determine there was difference in the average score of students' problem solving skills significantly before and after applying the problem solving learning model. The sample in the study consisted of 25 students Data were analyzed with descriptive statistics and inferential statistics using SPSS 21.0 for Windows. The results of this study were: (1) Improving the problem solving skills of students in class VIII at SMPN 39 Makassar who were taught using problem solving learning model obtained an N-Gain of 0.54 in the medium category. (2) There is a difference significant increase in the average score before and after the application of the problem solving learning model. This shows that the application of problem solving learning model can improve students' problem solving skills.